13x+12=6(10-5)+2(15+18)

Simple and best practice solution for 13x+12=6(10-5)+2(15+18) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x+12=6(10-5)+2(15+18) equation:


Simplifying
13x + 12 = 6(10 + -5) + 2(15 + 18)

Reorder the terms:
12 + 13x = 6(10 + -5) + 2(15 + 18)

Combine like terms: 10 + -5 = 5
12 + 13x = 6(5) + 2(15 + 18)

Multiply 6 * 5
12 + 13x = 30 + 2(15 + 18)

Combine like terms: 15 + 18 = 33
12 + 13x = 30 + 2(33)

Multiply 2 * 33
12 + 13x = 30 + 66

Combine like terms: 30 + 66 = 96
12 + 13x = 96

Solving
12 + 13x = 96

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 13x = 96 + -12

Combine like terms: 12 + -12 = 0
0 + 13x = 96 + -12
13x = 96 + -12

Combine like terms: 96 + -12 = 84
13x = 84

Divide each side by '13'.
x = 6.461538462

Simplifying
x = 6.461538462

See similar equations:

| 41*x=246 | | n-8=-110 | | 12+y=-32 | | 10x-13=-x+9 | | 3(2x-5)+6x-2= | | x^3-6x^2-48=0 | | -6(5x+5)=-180 | | y+-31=6 | | y+-43=-41 | | x+-18=-32 | | 16+3-1*3=10 | | -3(4b+1)=-63 | | 12.00+-2.00x=10.00 | | 3p^2-5p-18=0 | | 35x^2=-x+6 | | 6v+11=3v+8 | | x+-29=1 | | 37-2(c+3)=4(c+5)+c | | 57*3=2x | | 18x+7(5x-9)+5(2x+7)+9=2x+5 | | -x-5=2x-5 | | 11+x=-19 | | 6(5p-2)=138 | | x+-44=-81 | | 98(-3)+98(3)=y | | -2w+8=-4w | | x+9x+4=0 | | 2+4lnx=12 | | 4x-2+5x+4=2x-3x+3-4 | | 5.2k=3.7+12.9 | | n+1=n | | -13+-5x=-43 |

Equations solver categories